Single-cell RNA sequencing identifies inflammatory tissue T cells in eosinophilic esophagitis - Wen, Ting (J Clin Invest, 2019)
T cell heterogeneity is highly relevant to allergic disorders. We resolved the heterogeneity of human tissue CD3(+) T cells during allergic inflammation, focusing on a tissue-specific allergic disease, eosinophilic esophagitis (EoE). We investigated 1088 single T cells derived from patients with a spectrum of disease activity. Eight disparate tissue T cell subtypes (designated T1–T8) were identified, with T7 and T8 enriched in the diseased tissue. The phenotypes of T7 and T8 resemble putative Treg (FOXP3(+)) and effector Th2-like (GATA3(+)) cells, respectively. Prodigious levels of IL-5 and IL-13 were confined to HPGDS(+) CRTH2(+)IL-17RB(+)FFAR3(+)CD4(+) T8 effector Th2 cells. EoE severity closely paralleled a lipid/fatty acid–induced activation node highlighted by the expression of the short-chain fatty acid receptor FFAR3. Ligands for FFAR3 induced Th2 cytokine production from human and murine T cells, including in an in vivo allergy model. Therefore, we elucidated the defining characteristics of tissue-residing CD3(+) T cells in EoE, a specific enrichment of CD4(+) Treg and effector Th2 cells, confinement of type 2 cytokine production to the CD4(+) effector population, a highly likely role for FFAR3 in amplifying local Th2 responses in EoE, and a resource to further dissect tissue lymphocytes and allergic responses.